Ethical value of new reproductive choices in mitochondrial diseases - Moya, Graciela (Acta Bioethica, 2016)
Mitochondrial diseases are a clinically heterogeneous group of disorders with variable clinical features and high morbidity and mortality. As there are different hereditary patterns, complex implications in reproduction are expected; the recurrence risk may be about 25% in autosomal recessive inheritance, 4% in de novo mitochondrial mutations, and an uncertain, but high risk, when the mother is carrier of mitochondrial mutations. Thus, different preimplantation and prenatal diagnosis or assisted reproductive techniques are proposed to avoid the birth of children with these diseases. In this paper scientific and ethical implications of new assisted reproductive techniques offer to high risk families are describe and analyzed.